Faktor-Faktor yang Mempengaruhi Pemilihan Program Studi Diploma III Manajemen Tata Hidangan di Politeknik Pariwisata Bali - Ni Kadek Eni Juniari; I Nyoman Arcana; Putu Mira Astuti Pranadewi; I Nyoman Gede Agus Jaya Saputra (JURNAL BISNIS HOSPITALITI, 2022)
Vocational education in tourism during the pandemic is still the choice of people today in Indonesia, including the Food and Beverage Service Management Study Program (MTH Study Program) at the Bali Tourism Polytechnic (Poltekpar Bali). The MTH Study Program has a vision and mission to create professional and highly competitive human resources in the food and beverage service sector. The purpose of this study was to determine the factors that influence the selection of the D3 MTH study program and to analyze the strategic policy of the sustainability of the D3 MTH study program at Poltekpar Bali. This study used a quantitative descriptive analysis technique with purposive sampling as a sampling technique. The confirmed factors consist of 6 factors, namely quality, career, economy, family environment, community environment, and campus attractiveness with 20 indicators. This research was conducted for 3 months, from September to November 2020 with a total of 427 people as online respondents. The results showed that of these 6 factors, the majority of respondents stated that the career factor was the highest consideration in choosing the MTH Poltekpar Bali study program and the lowest was the family environment factor. Meanwhile, there are 7 strategic policies that can be carried out by the management of the Bali Poltekpar to improve community election decisions, especially high school and vocational high school graduates to choose the MTH Study Program at Poltekpar Bali as the first choice of college. The results of this study can be used as the basis for determining policies in the management and development strategy of the MTH Study Program at Poltekpar Bali.